Perspectives in the Molecular Mechanisms Underlying Anaphylaxis - Esteban, Vanesa; Skrabski, F.; Perales Chorda, C.; Puente Crespo, Y.; Muñoz Cano, R.; Cardona, V. (My University, 2025)
The complexity of anaphylaxis in terms of clinical features and etiology-pathogenesis makes it difficult to establish precise endotypes that correspond to specific phenotypes. Therefore, interest in unravelling the cellular and molecular mechanisms underlying anaphylactic reactions has grown. A large group of anaphylactic reactions are characterized by the classical immunological mechanism of type I hypersensitivity, which leads to IgE-mediated activation of mast cells and basophils. However, in recent decades, other relevant signaling pathways have emerged. These include IgG-associated neutrophil activation, complement activation, cyclooxygenase metabolism, and direct mast cell activation. In drug-induced anaphylaxis, the Mas-related G protein¿coupled receptor (MRGPRX2) plays an interesting role by directly triggering mast cell degranulation. In addition, contact, coagulation, and metabolic systems are activated, while homeostasis is altered, as evidenced by the modulation of proteins such as albumin, phospholipids, and apo-and lipoproteins. In all cases, the release of mediators and/or dysregulation of the systems has an impact on the endothelium, which is actively involved in the pathophysiology of the reactions. Furthermore, recent evidence points to extracellular vesicle-and microRNA-mediated communication between cellular compartments in anaphylaxis, and genetic factors, such as hereditary a-tryptasemia, are associated with risk of severe reaction. In summary, the recognition of cellular and molecular signaling mechanisms will enable better patient phenotyping and management in clinical practice. © 2025 Esmon Publicidad.
Keywords: Anaphylaxis, Immunoglobulins, Mechanisms, Epigenetic, Endothelium, Extracellular vesicles, miRNAs, Metabolites, a-Tryptasemia